Chloramine-T (N-chloro-p-toluenesulfonamide sodium salt), a versatile reagent in organic synthesis and analytical chemistry: An up to date review - Yogeesha N. Nayak; Santosh L. Gaonkar; Ebraheem Abdu Musad Saleh; Abdullah Mohammed A.L. Dawsari; Harshitha; Kakul Husain; Ismail Hassan (Journal of Saudi Chemical Society)
Chloramine-T (CAT), the sodium salt of N-chloro-p-toluenesulfonamide, is a low-cost mild oxidizing agent with a wide range of uses. Most importantly, it can be used in acidic, neutral, and basic conditions. As a result, it’s been widely used in chemistry, particularly in organic synthesis and analytical chemistry. Chloramine-T acts as a source of halonium cation and nitrogen anion and thus acts as base and nucleophile. It reacts with a wide range of functional groups and carries different molecular transformations. This paper thoroughly summarises and highlights the synthetic and analytical effectiveness of CAT. This study focuses on current developments as well as some older techniques in which CAT has been employed as an oxidizing agent. This review article stretches a comprehensive profile of the CAT reagent in organic synthesis and analytical chemistry, which will be very useful for further research exploration in this field.